1999
DOI: 10.1007/s001250051271
|View full text |Cite
|
Sign up to set email alerts
|

The relation of proinsulin and insulin to insulin sensitivity and acute insulin response in subjects with newly diagnosed Type II diabetes: the Insulin Resistance Atherosclerosis Study

Abstract: Simultaneously with insulin and C peptide, beta cells also secrete a small amount of proinsulin and its conversion intermediates [1]. Insulin and proinsulin cross-react in conventional insulin radioimmunoassays. Plasma proinsulin concentrations are considerably increased in patients with Type II (non-insulindependent) diabetes mellitus and constitute a substantial proportion of the total insulin-containing molecules [2±7]. Also subjects with impaired glucose tolerance (IGT) have higher proinsulin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 33 publications
2
52
1
1
Order By: Relevance
“…24 Plasma proinsulin has also been found to have stronger associations than insulin with hypertension, dyslipidemia, and impaired glucose tolerance. 25 Fasting proinsulin was found to be more strongly correlated to measurements of insulin resistance than to measurements of acute insulin response, similar to the pattern of fasting specific insulin, 26,27 whereas the fasting proinsulin to insulin ratio was proposed as a marker for insulin secretion. 27 Thus, rather than being directly associated with its cause, proinsulin may be a marker of an underlying metabolic disturbance predisposing to atherosclerosis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…24 Plasma proinsulin has also been found to have stronger associations than insulin with hypertension, dyslipidemia, and impaired glucose tolerance. 25 Fasting proinsulin was found to be more strongly correlated to measurements of insulin resistance than to measurements of acute insulin response, similar to the pattern of fasting specific insulin, 26,27 whereas the fasting proinsulin to insulin ratio was proposed as a marker for insulin secretion. 27 Thus, rather than being directly associated with its cause, proinsulin may be a marker of an underlying metabolic disturbance predisposing to atherosclerosis.…”
Section: Discussionmentioning
confidence: 74%
“…25 Fasting proinsulin was found to be more strongly correlated to measurements of insulin resistance than to measurements of acute insulin response, similar to the pattern of fasting specific insulin, 26,27 whereas the fasting proinsulin to insulin ratio was proposed as a marker for insulin secretion. 27 Thus, rather than being directly associated with its cause, proinsulin may be a marker of an underlying metabolic disturbance predisposing to atherosclerosis. 7 In vitro, proinsulin increases the plasminogen activator inhibitor-1 (PAI-1) production, 28 and in humans, plasma proinsulin was directly associated with PAI-1 concentrations.…”
Section: Discussionmentioning
confidence: 74%
“…It has been shown that exercise reduces the plasma concentrations of triglycerides and increases the concentrations of HDL cholesterol [11]. A change in proinsulin concentrations could reflect a change in insulin sensitivity [23,24]. Insulin sensitivity and glucose disposal are improved by exercise [11].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity was inversely associated with mortality from cardiovascular diseases (and all causes). The association was weakened when adjusted for insulin, proinsulin and split proinsulin, factors related with insulin resistance [23,24], indicating that these metabolic factors could mediate the higher risk of mortality among sedentary individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation